E-methods in literary production: integrating e-learning in creative writing - Noraini Md Yusof, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
This paper discusses the integration of e-learning in creative writing. The online approach to the teaching of creative writing takes into account today’s Malaysian youth and their fascination with computer technology. It is this appeal of innovation in electronics and knowledge that leads an educator to design an on-line approach to a creative writing course. The theoretical construct used to support the discussion is Anderson’s theory that on-line learning is knowledge-, community-, assessment-, and learner-centered. The writer, who is also the course developer, analyses a poetry-writing activity, which students undertake, and the e-portfolio used in the course. To analyze the processes involved in this creative writing exercise Macherey’s (1978) Theory of Literary Production is adapted and utilized. This theory, which regards literary production as a process imitating that of a production line, provides the methodology and conceptual framework for analyzing the raw materials collected by the students and their transformation during the writing process. This paper thus addresses the benefits of e-learning in a creative writing context.